Structuration de l’espace professionnel et insertion en emploi des diplômées et diplômés du cégep technique - Bourdon, Sylvain (Canadian Journal of Counselling and Psychotherapy, 2007)
Today's economic context impacts the world in which young people transiting from school to work have to carve themselves a place. The diversity in itineraries of young graduates—from full time employment to pursuing further studies; from precarious jobs to unemployment— though, is not totally random. We suggest that the variety of difficulties and the multiple alternatives faced by young graduates are the effect of the differential structuration of professional spaces opened by their diplomas. An analysis of the behaviour of more or less closed professional spaces in a context of crisis shows, in each case, different openings for the young graduates.